Phelan–McDermid Syndrome in Pediatric Patients With Novel Mutations: Genetic and Phenotypic Analyses - Chen, Liang; Yao, Zhi-ye; Wu, Xiangtao; He, Shao-ru; Liu, Yu-mei; Wang, Xue-yan; Cao, De-zhi; Yang, Xing-kun; Zhao, Jian-bo; Ren, Zi; Li, Hong; Pei, Zheng; et al. (Frontiers in Pediatrics, 2022)
Background: Phelan–McDermid syndrome (PMS) is an uncommon autosomal dominant inherited developmental disorder. The main characteristics are hypotonia, intellectual disability, autism spectrum disorder, autism-like behaviours and tiny facial deformities. Most cases are caused by the deletion of the 22q13 genome region, including the deletion of SHANK3. Methods: Genetic and phenotype evaluations of ten Chinese paediatric patients were performed. The clinical phenotypes and genetic testing results were collected statistically. We analysed the deletion of the 22q13 genomic region and small mutations in SHANK3 (GRCh37/hg19) and performed parental genotype verification to determine whether it was related to the parents or was a novel mutation. Results: The age of the patients diagnosed with PMS ranged from zero to twelve years old. Nine of the paediatric patients experienced Intellectual Disability, language motion development delay and hypotonia as prominent clinical features. One subject had autism, two subjects had abnormal electroencephalogram discharge and one subject was aborted after foetal diagnosis. Three patients had a SHANK3 mutation or deletion. All but the aborted foetuses had intellectual disability. Among the ten patients, the 22q13.3 deletion occurred in seven patients, with the smallest being 60.6 kb and the largest being greater than 5.5 Mb. Three patients had heterozygous mutations in the SHANK3 gene. Conclusion: All ten patients had novel mutations, and three of these were missense or frameshift mutations. For the first time reported, it is predicted that the amino acid termination code may appear before protein synthesis. The novel mutations we discovered provide a reference for clinical research and the diagnosis of PMS.